Photonic molecules modes in resonantly coupled spherical microcavities with semiconductor nanocrystals - Bradley, Louise; Donegan, John; Rakovich, Yury; Gerlach, Matthias; Connolly, T.; Boland, J.J.; Gaponik, Nikolai; Rogach, A.L. (My University, 2005)
We present a detailed study of the localized coupled-cavity modes in a photonic molecule formed from two dielectric spherical microcavities with CdTe nanocrystals, which show a multi-peak narrowband modal structure resulting from lifting of the mode degeneracy with respect to the azimuthal quantum number. The feasibility of photonic molecules as the basis for a multi-channel, wavelength-tunable optical delay device is analysed.
Proceedings of SPIE, Opto-Ireland 2005: Optoelectronics, Photonic Devices, and Optical Networks
SPIE Opto-Ireland 2005
Keywords: Couples microcavities; Semiconductor nanocrystals; Whispering gallery modes; Mode degeneracy; Optical delay